The landscape of online news regarding genetically modified foods: A cross-sectional study. Issue 2 (June 2023) - Samuel, Lalitha; Basch, Sawyer I.
Background: There has been substantial debate surrounding the use of genetically modified foods (GMFs). Aim: The purpose of this study was to describe the content of news articles covering GMFs. Methods: A search was completed on Google News using the key words "genetically modified foods" and the resulting 100 English-language news articles were analyzed for content. Results: Only 26% of the articles analyzed were from professional or government sources. Among all content categories, definition or explanation of GMFs with a featured product as an example had the highest coverage, being addressed in 74% of the sample. Identification of GMFs from food labels (p = .001), was significantly associated with the source of the article (p > .05). Conclusions: Opportunities exist for scientists, educators, and health experts to present evidence-based and science-based information, with a balanced emphasis on the risks and benefits of GMFs to help consumers to make well-informed choices.